PWE-072 Outcomes of single or sequential dual modality loco-regional therapies in hepatocellular carcinoma. (17th June 2017) - Cross, T; Swaminathan, M; Kibriya, N; Evans, J
Abstract : Introduction: Hepatocellular carcinoma (HCC) in western populations commonly occurs in the context of cirrhosis. Staging of disease has been based primarily on the BCLC classification in the UK. Patients not fit for OLT or liver resection in stage A disease have been offered ablations whilst patients with intermediate stage disease B, have been offered trans-arterial chemoembolization (TACE). Aims: To assess outcomes from patients offered single modality or dual modality therapy for HCC, and to identify prognostic factors. Method: A single centre study of patients from the Royal Liverpool Hospital from 2003 to 2016. Patients receiving loco-regional therapy were identified from the departmental HCC database. Patient characteristics collected included, age, gender, aetiology, standard biochemistry, BCLC stage, ECOG performance status, tumour size and number, and treatments offered: RFA alone, RFA-TACE, TACE alone and TACE -RFA. The primary outcome measure was survival, calculated using the log-rank method. Results: Out of 295 patients in our cohort, 96 patients were identified who had ablation (radiofrequency (pre-2010) or microwave ablation (from 2010), TACE, or a combination of the 2. The median age was 67 (57-74), the BCLC grade was 0=9 (9%), A 42 (44%), B 35 (36%), C 9 (9%), D 1 (1%). Disease aetiology was ALD=27, HBV=4, HCV=21, NASH=27, haemochromatosis=5, ALD + viral=5, others=7. HAP score was available in 85 patients HAP A=38, B, 24, C=21, D=2. A total of 143 TACE and 154 ablation procedures were performed. The median survival for ablation alone 37 mths (26-48), RFA-TACE 38 mths (33-43), TACE alone 16 (15-17), and TACE-RFA 34 mths (22-46), log rank 13.3., p=0.004. Survival using HAP score was HAP A 38 mths(24-52), HAP B 35 mths (20-50), HAP C 12 mths (7-17), HAP D 2 (1–3), log rank 68.1, p<0.0001. Conclusion: Our data suggests that patients, who cannot be down-staged with TACE to receive ablation, do worse than patients with earlier stage disease who progress after ablation alone, or who receive TACE following an ablation. This supports the use of dual sequential therapy where indicated. The HAP score is a useful tool to identify patients most likely to benefit from loco-regional treatments. Disclosure of Interest: None Declared